Improving The Implementation Of The Profile Of Pancasila Student Strengthening Projects With Example - Ari Murniasih; Rahmat Mulyono (Fakultas Agama Islam Universitas Wiralodra Indramayu, 2023)
The influence of the school principal's example in improving the implementation of the Pancasila Student Profile Strengthening Project through increasing teacher self-confidence in the ABA Karangmojo XX Kindergarten Mobilization School, increasing the ability of teachers to prepare and carry out the process of the Pancasila Student Professional Strengthening Project and increasing teacher motivation to learn and increasing professional skills in run errands. The Principal of ABA Karangmojo XX Kindergarten Activator School is improving the implementation of the Pancasila Student Profile Strengthening Project by exemplary to open opportunities for the creation of complementary two-way communication. This approach is transformed into operational steps in the form of concrete steps. According to Ki Hajar Dewantara's educational concept, the among system consists of three things, namely